Investing more in universal social protection: Applying international social security standards in social protection policy and financing - Mira Bierbaum; Valérie Schmitt (International Labour Organization (ILO), 2022)
The COVID-19 pandemic has exposed significant gaps in the coverage, comprehensiveness and adequacy of social protection systems worldwide. These gaps have jeopardized the health, incomes and jobs of billions of people. Closing these protection gaps, facilitating faster and inclusive socio-economic recovery and enhancing resilience against future shocks requires more investment in social protection. Yet, more investment alone is not sufficient; countries also need to invest better in universal social protection, that is, to ensure that investments in social protection contribute to building systems that are aligned with international social security standards, in particular the Social Protection Floors Recommendation, 2012 (No. 202), working in tandem with the Social Security (Minimum Standards) Convention, 1952 (No. 102). This working paper is intended for a broad audience and outlines how the guidance provided by Recommendation No. 202 contributes to building nationally owned social protection systems that comprehensively and adequately protect the population and leave no one behind, are financially sustainable and socially just and rely on sound management and good governance.
Keywords: I3; H3; H53; H55; F53; 330; social protection; social security systems; social protection floors; international social security standards; social security contributions; public expenditure; fiscal space; social protection financing; solidarity; developing countries; Sustainable Development Goals (SDGs)